Perbandingan Metode Beban Seismik Statis Ekuivalen, Spektrum Respons, dan Riwayat Waktu pada Kubah - Yasa, P. Adi; Kedaton, Kadek Hindhu Putra; Prayoga, Made Hendra; Bhisama, Ida Bagus Prastha (Universitas Islam 45, 2025)
Dome structures are known to have good seismic resistance. However, the Indonesian National Standard (SNI) does not extensively discuss the earthquake loading methods that can be used as references in designing dome structure elements. This study aims to identify the most appropriate earthquake loading method for buildings with a dome shape. Several earthquake loading methods are compared, including equivalent static analysis, spectral response, and time history. A case study is used, involving a dome structure with a span of 60 meters, a height of 30 meters, and made of A36 steel. The earthquake source location is taken from Denpasar, Bali. The analysis includes base shear, deformation comparison, and internal forces for all three loading methods. The results show differences in structural responses between the equivalent static, response spectrum, and time history methods. The response spectrum method is considered more suitable for dome structure modeling in terms of safety, while the equivalent static method is more appropriate for practical considerations and ease of design.